READING INTEREST, TEXT TYPES AND READING COMPREHENSION OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF FKIP SRIWIJAYA UNIVERSITY - Dian Mardasari (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The aims of this study were to describe the reading interest, text types and reading comprehension, to find out whether or not there was significant correlation between students’ reading interest and their reading comprehension, to find out whether or not there was significant difference in reading comprehension in terms of the text types, to find out how much each text types contributed in reading comprehension, to find out whether or not there was significant difference in reading interest in terms of the text types; and to find out how much each text types contributed in reading interestSeventy three students of the English Education Study Program of Faculty of Teacher Training and Education within Sriwijaya University in the academic year of 2014/2015 were selected as the sample by means of total population sampling. The data were collected through the use of Reading Interest Questionnaire and a set of reading comprehension test. The data were analyzed by using Pearson Product Moment correlation coeficient and Independent Sample t-test. The results were as follows: 1) most students interested in narrative text and had good and average scores on reading comprehension, 2) the correlation between reading interest and reading comprehension was significant, 3) there was significant difference in students’ reading comprehension in terms of text types, 4) expository text gave more contribution than narrative text, 5) there was significant difference in students’ reading interest in terms of text types, and 6) narrative text gave more contribution than expository text.Key words: reading interest, text types, reading comprehension, university students